Answer:
x = 0, x = -4, and x = 6
Step-by-step explanation:
To find the zeros of this polynomial, we can begin by factoring out a common factor of each term. 'x' is a common factor. We can distribute this variable out, giving us:
f(x) = x(x²- 2x- 24)
Now, factor the polynomial inside of the parenthesis into its simplest form. Factors of -24 that add up to -2 are -4 and 6.
f(x) = x( x + 4) (x - 6)
From this, we can derive the zeros x = 0, x = -4 and x = 6.
What graph? Show me in the comments if you can.
Answer:
y = 12
Step-by-step explanation:
Use the equation y = kx
Plug in x and y to find k:
2 = k(16)
1/8 = k
Then, plug in 1/8 as k and 96 as x to find y:
y = 1/8(96)
y = 12